2015
DOI: 10.12691/ajnr-3-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of Nocturnal Enuresis on Self-esteem of School Children

Abstract: Bedwetting is the cause of significant psychosocial stress especially in older children. Aim: The study aimed to assess the psychological impact of nocturnal enuresis on self-esteem of school children. Design: Descriptive research design was used in this study. Setting: The study was conducted in El-Menoufya University Hospital, in Egypt, which consisted of 18 outpatient clinics. The pediatric outpatient clinic of Shebin El-Kom, El-Menoufia University Hospital it is general pediatric outpatient clinic for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The present study results also revealed that the highest percentage of children with enuresis is quite common in the society of El Fayoum Governorate; where education is a critical factor that may affect the mothers' ability to use booklet to gain the required information although they are having enough time while may give them an opportunity to provide good care and apply gained practice about child enuresis. A similar finding was demonstrated in the study of Elbahnasawy and Elnagar (2015) (14) who proved that a higher relative risk of enuresis in children was observed in families with a father with a lower education and a mother with a relatively lower education. In the same line, another previous research carried out by Inan, et al (2008) reported that the higher prevalence of enuresis occurs in families where mother has a lower level of education.…”
Section: Discussion:-supporting
confidence: 85%
“…The present study results also revealed that the highest percentage of children with enuresis is quite common in the society of El Fayoum Governorate; where education is a critical factor that may affect the mothers' ability to use booklet to gain the required information although they are having enough time while may give them an opportunity to provide good care and apply gained practice about child enuresis. A similar finding was demonstrated in the study of Elbahnasawy and Elnagar (2015) (14) who proved that a higher relative risk of enuresis in children was observed in families with a father with a lower education and a mother with a relatively lower education. In the same line, another previous research carried out by Inan, et al (2008) reported that the higher prevalence of enuresis occurs in families where mother has a lower level of education.…”
Section: Discussion:-supporting
confidence: 85%
“…But we could not rule out the possible debilitations it could cause in children that may affect their growth and development. 51,52 With the worldwide prevalence of epilepsies in children, it is necessary to conduct more studies on this rare effect of the AEDs, which is known as a potent treatment option for various epilepsies.…”
Section: Resultsmentioning
confidence: 99%
“…These results go in line with Salem, et al, [19] who reported that about two-thirds of mothers were housewives, resides in a rural area, and the minority of them was divorced. In addition, El bahnasawy and Elnagar [2] who proved that a higher relative risk of enuresis in children was observed in a mother with relatively lower education. This is in accordance with the current study results.…”
Section: Discussionmentioning
confidence: 98%
“…Nocturnal enuresis (bedwetting or urinary incontinence during sleep) has a view of an iceberg as a public health problem which can lead to profound loss of self-esteem, self-perception and poor inter-personal relationship to the affected children. It occurs especially with low income, smaller age, family history of enuresis and history of urinary tract infection [1,2]. It is classified into primary enuresis (75%) when nocturnal urinary continence has not been achieved since birth, and secondary enuresis (25%) when bed-wetting occurs in a child with at least 6 months of nighttime dryness.…”
Section: Introductionmentioning
confidence: 99%